Patterns of insecticide uses and its impact on the health of the farmers in Tangail district of Bangladesh (Annals of Bangladesh Agriculture, 2024)
Appropriate and judicious application of insecticide is the most effective measure of crop protection against the injury and damage of insect pests. However, the tendency of the farmers is to apply insecticide without maintaining proper dose, time and precautionary measures. This study was conducted in Dhanbari and Madhupur upazilas of the Tangail district during July to October 2020 to find out the patterns of insecticide use on summer vegetables and the potential risks of insecticides on the health of farmers. Data were collected from randomly selected 120 farmers through a pre-tested questionnaire. The majority of farmers within the study area obtained information regarding specific insect pests and the recommended insecticide from local retailer shops 81.7%), whereas information on insecticide dosage was primarily gathered from experts (91.7%). In the study area, farmers applied insecticides once/twice a season (66.7%). The survey report showed that 60.0% of the farmers applied insecticides without reading the label information, while all the farmers applied insecticides using hand driven sprayer machine between the hours of 10 am to 3 pm. Results revealed that 63.3% of the farmers took a moderate protective measures, but 93.3% did not consider pre-harvest Interval (PHI). A considerable portion of farmers (48.3%) kept pesticide bottles and packaging alongside other inputs, while most respondents (96.6%) disposed of these items in the fields. It was found that 70.0% of the farmers were acquainted with health hazards, 56.6% knew about water pollution, 54.1% knew about reduction of pollinators due to insecticide application. Based on the perspectives of the participants, it was also found that, 60.0% farmers suffered from physical weakness, 55.0% suffered in loss of appetite, 38.3% suffered in eye irritation, 28.3% experienced in body itching, and 12.7% suffered urinary and sexual disorder.Ann. Bangladesh Agric. (2023) 27 (1): 31-39